Scoliosis Orthopedic Surgery Combined With Nusinersen Intrathecal Injection Significantly Improved the Outcome of Spinal Muscular Atrophy Patient: A Case Report - Xu, Beiyu; Wei, Cuijie; Hu, Xiao; Li, Wenzhu; Huang, Zhen; Que, Chengli; Qiu, Jianxing; Li, Chunde; Xiong, Hui (Frontiers in Neurology, 2022)
Background: Spinal muscular atrophy (SMA) is an autosomal recessive disorder caused by pathogenic variation of the survival motor neuron (SMN) 1 gene. Symptoms include progressive limb muscle weakness, atrophy, and severe scoliosis. Nusinersen is an antisense oligonucleotide which can enhance the production of the SMN protein. Here we report a case with scoliosis who received orthopedic surgery combined with Nusinersen intrathecal injections. Case: Scoliosis orthopedic surgery followed by Nusinersen intrathecal injections was given to a 16-year-old girl who had thoracic and lumbar scoliosis and type 3 SMA. Surgery was performed for T3-S2 posterolateral fusion (PLF), with her osseous channel left on vertebral laminae of L3-L4. The balance of the spine and pelvis was significantly improved and the height increased by 9cm. Lumbar puncture was conducted with local anesthesia under ultrasound and CT guidance through the laminae channel and Nusinersen was injected successfully. Comparing the two approaches, real-time ultrasound guidance for intrathecal Nusinersen injections after spinal surgery is preferred, however, CT guidance is an alternative if the initial puncture procedure is difficult. After the above multidisciplinary treatment, a good effect was achieved, as demonstrated by a 2-point increase in RULM and MFM32 scores two months later. Conclusion: Scoliosis orthopedic surgery combined with Nusinersen intrathecal injection is an effective procedure for SMA patients with scoliosis.